Dual-polarization airborne lidar observations of polar stratospheric cloud evolution - Poole, L. R.; Mccormick, M. P.; Kent, G. S.; Hunt, W. H.; Osborn, M. T. (1990)
Dual-polarization 0.532 micron lidar data show systematic polar stratospheric cloud (PSC) evolution along a portion of the Airborne Arctic Stratospheric Expedition DC-8 flight of January 31, 1989. This flight leg was roughly aligned with air parcel motion on isentropic surfaces from 400-500 K, where the local adiabatic cooling rate was about 20 K/day. Type 1 PSCs show low depolarization ratios and scattering ratios which approach intermediate limiting values as ambient temperature decreases. These data suggest that Type 1 particles formed by rapid cooling may be nearly spherical and are restricted in size by partitioning of a limited HNO3 vapor supply among many competing growth sites. Type 2 PSCs appear at temperatures below estimated local frost points with increases in depolarization and scattering typical of larger ice crystals.